2018
DOI: 10.1097/scs.0000000000004685
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results for a One-Stage Surgery Technique for Patients With Craniofacial Plexiform Neurofibroma

Abstract: The surgical technique could achieve good surgical outcomes in both functional and cosmetic terms. Additionally, the relatively objective evaluation technique based on Mimics software could be a more convincing method for evaluating the surgical outcomes of craniofacial patients with PNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Furthermore, PNFs may present in the form of diffuse enlargement of the affected body region (11,29,32). Current surgical experience has shown that recurrence rates for BPNSTs range from 1.3% to 54% and are higher in pediatric PNFs (29,30,32,(34)(35)(36)(37). Outcome is largely influenced by tumor histopathology, type of mutation and tumor location (34,(38)(39)(40).…”
Section: Treatment Of Pnstsmentioning
confidence: 99%
“…Furthermore, PNFs may present in the form of diffuse enlargement of the affected body region (11,29,32). Current surgical experience has shown that recurrence rates for BPNSTs range from 1.3% to 54% and are higher in pediatric PNFs (29,30,32,(34)(35)(36)(37). Outcome is largely influenced by tumor histopathology, type of mutation and tumor location (34,(38)(39)(40).…”
Section: Treatment Of Pnstsmentioning
confidence: 99%
“…1 They often lack function and aesthetic value, thereby negatively affecting quality of life. 2 There is no specific treatment for NF1, and clinical manifestations are treated individually. Surgery is the preferred treatment for plexiform neurofibromas, but the significant vascularization of the tumor and the consequent possibility of large intraoperative hemorrhages make the procedure difficult.…”
Section: Introductionmentioning
confidence: 99%